PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP MUTU PENDIDIK - Siti Aimah; Nur Laeliyah (Institut Agama Islam Darussalam Blokagung, 2021)
The purpose of this study was to determine the management of MTs al-Amiriyyah Blokagung Tegalsari Banyuwangi's human resources, about the quality of MTs al-Amiriyyah Blokagung educators, is there any influence of human resource management on the quality of MTs al-Amiriyyah Blokagung Tegalsari Banyuwangi educators, the effect of human resource management on the quality of MTs al-Amiriyyah Blokagung Tegalsari Banyuwangi educators.This research uses descriptive quantitative method.The data collection methods used in this study are questionnaire, observation, documentation. As for the data validity test using the product moment formula, to find the reliability of the data using the formula Cornbach, Alpha. Then for hypothesis testing using the T test and F test, for the normality test using the Kolmogorov-Smirnov formula. In data analysis using Simple Linear Regression analysis.The results of this study indicate that the management of human resources on the quality of MTs al-Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 Academic Year is classified as good, because the T test results of 81.524> 1.305 t tables, which means Ha is accepted. there is an influence of human resource management on the quality of MTs al-Amiriyyah Blokagung Tegalsari Banyuwangi educators by 99.5% while the remaining 0.05% is influenced by other variables not examined, which means the effect of human resource management on the quality of MTs al-Amiriyyah Blokagung educators is good.